2021
DOI: 10.1093/ntr/ntab110
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Enrollment of Older Smokers in Six Smoking Cessation Trials in the Lung Cancer Screening Setting: The Smoking Cessation at Lung Examination (SCALE) Collaboration

Abstract: Significance Increased rates of smoking cessation will be essential to maximize the population benefit of low-dose CT screening for lung cancer. The NCI’s Smoking Cessation at Lung Examination (SCALE) Collaboration includes eight randomized trials, each assessing evidence-based interventions among smokers undergoing lung cancer screening (LCS). We examined predictors of trial enrollment to improve future outreach efforts for cessation interventions offered to older smokers in this and other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…To date, some of these studies have provided evidence for the integration of cessation in the lung screening context. Offering multiple accrual methods and at multiple points over the screening may help to engage the smokers, and providing pharmacotherapy options promotes enrolment [118]. Retention and treatment engagement differ on demographic, clinical, and psychological characteristics (e.g., number of cigarettes smoked per day, education, worry about lung cancer, screening results) [119].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…To date, some of these studies have provided evidence for the integration of cessation in the lung screening context. Offering multiple accrual methods and at multiple points over the screening may help to engage the smokers, and providing pharmacotherapy options promotes enrolment [118]. Retention and treatment engagement differ on demographic, clinical, and psychological characteristics (e.g., number of cigarettes smoked per day, education, worry about lung cancer, screening results) [119].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…To date, some of these studies have provided evidence for the integration of SCP in the lung screening context. Offering multiple accrual methods and at multiple points during the screening regimen may help to engage current smokers, and, by providing pharmacotherapy options, to promote enrolment [ 121 ]. As expected, treatment engagement and retention reflect demographic, clinical, and psychological characteristics (e.g., number of cigarettes smoked per day, education, worry about LC, and screening results) [ 122 ].…”
Section: Open Questionsmentioning
confidence: 99%
“…To determine how best to integrate smoking cessation treatment in the lung screening setting, the National Cancer Institute initiated the Smoking Cessation at Lung Examination (SCALE) collaboration [7] that is comprised of eight clinical trials, including Georgetown's Lung Screening, Tobacco, and Health (LSTH) trial (NCT03200236) [8][9][10][11][12]. To date, several SCALE-related papers have assessed predictors of enrollment and retention [7,10,13].…”
Section: Predictors Of Enrollment and Retention In Smoking Cessation ...mentioning
confidence: 99%
“…To determine how best to integrate smoking cessation treatment in the lung screening setting, the National Cancer Institute initiated the Smoking Cessation at Lung Examination (SCALE) collaboration [7] that is comprised of eight clinical trials, including Georgetown's Lung Screening, Tobacco, and Health (LSTH) trial (NCT03200236) [8][9][10][11][12]. To date, several SCALE-related papers have assessed predictors of enrollment and retention [7,10,13]. In a cross-project analysis of enrollment across six of the eight SCALE trials (n = 6285), we found that participants were more likely to be Black or African American, were less likely to be of Hispanic ethnicity, and were significantly younger compared to their counterparts among those who declined enrollment or could not be reached [7].…”
Section: Predictors Of Enrollment and Retention In Smoking Cessation ...mentioning
confidence: 99%
See 1 more Smart Citation